It may work well to solve this system by

*elimination*. To eliminate y as a variable, multiply the first equation by 4 and the second by 3. Add the results. 4(4x - 3y) + 3(3x + 4y) = 4(14) + 3(23) 16x - 12y + 9x + 12y = 56 + 69 (use the distributive property to eliminate parentheses) 25x = 125 (collect terms) x = 5 (divide by 25) Now, we can use this to find y. Substituting into the second equation, we get 3(5) + 4y = 23 (put 5 where x was in the equation) 4y = 8 (subtract 15 from both sides) y = 2 (divide by 4)**The solution is (x, y) = (5, 2).**__Check__4(5) - 3(2) = 14 20 - 6 = 14 (first equation checks) 3(5) + 4(2) = 23 15 + 8 = 23 (second equation checks)